Health condition of Łódzkie province inhabitants compared to Polish citizens - Suwała, Małgorzata; Gerstenkorn, Andrzej (Polish Journal of Public Health, 2012)
Introduction. Systematic study of the population’s health condition is a primary goal of national healthcare and should be a base for taking significant resolutions as far as the state health policy is concerned. The comparison of the main negative indicators of the Poles’ health condition broken down by the province shows a vast diversity. Aim. The aim of the study is to present the current health situation of the Łódzkie province. Material and methods. The study uses the information about health condition and chosen factors of Poland’s health situation by the province included in the publications of the Central Statistical Office, National Institute of Hygiene, Regional Centre of Public Health in Łódź, the Government Population Council in the years 2007-2010. Results. It is worth noticing that Łódzkie province has the highest percentage of retirement age population in Poland (18.5%, Poland 16.5%), a very high feminization ratio – 110.2 (Poland 107.1) as well as the lowest population growth factor -2.24‰ (Poland +0.9). The overall standardized mortality rate was (2010) at 1017.0/100 thousand of people (Poland 784.2). Deaths due to cardiovascular system failure comprised 46% of all deaths, however, the standardized mortality rate in Łódzkie province was the highest in Poland and amounted to 509.8/100 thousand people (Poland 449.6). The life expectancy of Łódzkie province inhabitants was the lowest in Poland for both males and females, and amounted to 70.1 and 79.4 years in 2010. The incidence of viral hepatitis and tuberculosis, as well as road safety coefficients, are also very low in the Łódzkie province. Conclusions. The poor health condition is influenced to a great extent by socio-demographic population structure, feminization and progressive population aging. In recent years, in the Łódzkie province, the general standardized mortality rate, as well as the number of deaths due to cardiovascular diseases, external causes and diseases of the digestive system, have been the highest in Poland.